2012
DOI: 10.1063/1.4734983
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature electromechanical and magnetic investigations of ferroelectric Aurivillius phase Bi5Ti3(FexMn1−x)O15 (x = 1 and 0.7) chemical solution deposited thin films

Abstract: Aurivillius phase thin films of Bi5Ti3(FexMn1−x)O15 with x = 1 (Bi5Ti3FeO15) and 0.7 (Bi5Ti3Fe0.7Mn0.3O15) on SiO2-Si(100) and Pt/Ti/SiO2-Si substrates were fabricated by chemical solution deposition. The method was optimized in order to suppress formation of pyrochlore phase Bi2Ti2O7 and improve crystallinity. The structuralproperties of the films were examined by x-ray diffraction, scanning electron microscopy, and atomic force microscopy. Optimum crystallinity and pyrochlore phase suppression was achieved b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Note here, when Mn doping content is 0.6, many experiments were tried to synthesize pure Mn-doped BTFO compound by adjusting the sintering factors but we failed. However, when the Mn doping content is equal or less than 0.5, all powder diffraction peaks of these BTMFO samples can be indexed by JCPDF 82-0063, which is in accordance with four-layer Aurivillius BTFO phase, and also consistent with those of BTFO ceramics in other literatures [3][4][5][6]. The results indicated that Mn-doped BTFO compounds with Aurivillius phase can be obtained when the Mn-doping content is less than 0.5, while impurities appear obviously even in the XRD limit of precision when Mn-doping content x is beyond 0.5.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Note here, when Mn doping content is 0.6, many experiments were tried to synthesize pure Mn-doped BTFO compound by adjusting the sintering factors but we failed. However, when the Mn doping content is equal or less than 0.5, all powder diffraction peaks of these BTMFO samples can be indexed by JCPDF 82-0063, which is in accordance with four-layer Aurivillius BTFO phase, and also consistent with those of BTFO ceramics in other literatures [3][4][5][6]. The results indicated that Mn-doped BTFO compounds with Aurivillius phase can be obtained when the Mn-doping content is less than 0.5, while impurities appear obviously even in the XRD limit of precision when Mn-doping content x is beyond 0.5.…”
Section: Resultssupporting
confidence: 80%
“…Single-phase multiferroic materials with Aurivillius structure of the general formula Bi 4 Bi n À 3 Ti 3 Fe n À 3 O 3n þ 3 (n Z 4) have been widely studied in recent years because of the coexistence of ferroelectric order and magnetic order [1][2][3][4][5][6][7][8], and especially the associated electric/magnetic polarization coupling between the two different orders [9][10][11]. This could drive Aurivillius family to be qualified in new application fields, such as magnetic sensors, multi-state storages and spintronics and so on, besides ferroelectric random access memory (FeRAM) and piezoelectric actuators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we report the first magnetic investigations of Bi 5 19 The films were spin-coated on a-quartz substrates (42.75 6 15'ST-Cut) by a commercial spinner (spin coater KW-4A, Chemat Technology) operating at 4500 rpm for 30 s. Quartz substrates (350 lm thick) were chosen for their low diamagnetic contribution. Excess solvents and residual organics were removed from the films by baking on a calibrated hot plate at 300 6 5 C for approximately 10 min.…”
mentioning
confidence: 99%
“…22,35 Ferroelectric polarization in these materials is strongly hindered by additional impurity phases (such as pyrochlore). 23 These microstructural defects can be overcome by using optimised growth processes. For instance, the deposition of highly textured, oriented and uniform thin films can in principle extensively improve desired physical properties such as ferroelectric polarization, in material systems where the polarization is dependent on crystal orientation.…”
Section: Introductionmentioning
confidence: 99%